Help, Prejudice and Headscarves - Luis Artavia-Mora; Arjun S. Bedi; Matthias Rieger (Institute of Labor Economics (IZA), 2018)
This paper employs a natural field experiment in the Netherlands to test whether individuals intuitively help strangers with different group identities. We implement time manipulations in an everyday task to stimulate intuitive versus deliberate decision-making and thereafter examine helpfulness towards a female stranger with in-group (native) or out-group (Muslim) appearance. We find that time delay decreases helping rates. In contrast, regardless of time manipulation, out-group appearance does not influence helping rates. Overall, subjects are intuitively predisposed to help, independent of identity. We discuss our findings with respect to the literature on in-group favoritism and the cognitive origins of human cooperation.
Keywords: D03; D63; D64; 330; help; cooperation; in-group favoritism; Muslim; dual-process of cognition; natural field experiment; The Netherlands